Research for establishing conditions when a body mesurements can be obtained from a photograph - Nguyen , Thị Ngọc Quyên; Huynh, Văn Trí (Journal of Technical Education Science, 2015)
Indirect measurement from the image in the process: taking pictures with the camera, followed by image processing, extraction landmark and body size. This is a measure of low cost, easy to move, easy to use, is a new trend for anthropometric studies in Vietnam. In this paper, the author will set the conditions for photography 2D to improve the quality of the quality of the input image for indirect measurement system from image